Dietary complex probiotic supplementation changed the composition of intestinal short-chain fatty acids and improved the average daily gain of weaned piglets - Zhao, Jianfei; Xie, Zhuoya; Zheng, Meiling; Tang, Wenjie; Diao, Hui; Yin, Heng (Frontiers in Veterinary Science, 2024)
In this study, a total of ninety-six Duroc × Landrace × Yorkshire weaning weaned piglets with an initial body weight (BW) of 8.56 ± 0.53 kg were employed in a randomized complete block design for a 28-day experiment. Pigs were randomly divided into two treatment groups: the control group (CON) and the complex probiotic group (CON + 0.2% probiotics), respectively. The study found that through the 28-day experiment, the average daily gain (ADG) of the complex probiotic group was significantly higher than that of the CON (P < 0.05). However, compared with the CON, the feed conversion efficiency significantly decreased on days 0-14 (P < 0.05). The addition of dietary complex probiotic significantly increased the villus height (VH) of duodenum and ileum, acetate, propionate, butyrate and total short-chain fatty acids (SCFAs) in faeces, and decreased fecal methyl mercaptans, acetic acid and CO2 (P < 0.05). It concluded that feeding weaning weaned piglets 0.2% complex probiotic increased the VH of duodenum and ileum, as well as and alterchanged the content of SCFAs in faeces, . This ultimately led to an increase inwhich could be attributed to the increase of ADG.